Beyond the iconic protest images: the performance of 'everyday life' on social media during Gezi Park. (4th May 2019) - McGarry, Aidan; Jenzen, Olu; Eslen-Ziya, Hande; Erhart, Itir; Korkut, Umut
ABSTRACT: Using the Gezi Park protests as a case study this article considers the performative component of protest movements including how and why protestors actively produce protest activity 'on the ground' and how this is expressed through visual images. It looks beyond iconic images which appear as emblematic of the protest and instead shifts our focus to consider the more 'everyday' or mundane activities which occur during a protest occupation, and explores how social media allows these images to have expressive and communicative dimensions. In this respect, protests can be performed through humdrum activities and this signifies a political voice which is communicated visually. The research is based on visual analysis of Twitter data and reveals methodological innovation in understanding how protestors communicate.